(untitled) (THE ACADEMIA, 2025)
This study explores the impact of Management Accounting Practices (MAPs) on organizational performance in Nepalese commercial banks, focusing on budgeting, decision-making, costing, performance evaluation, benchmarking, and Time-Driven Activity-Based Costing (TDABC). A quantitative research design was employed, with data collected through structured questionnaires distributed to branch managers and customers. Out of 560 distributed questionnaires, 345 responses were analyzed for both managers and customers. The findings reveal a strong positive association between MAPs and organizational performance. Budgeting was identified as a key driver for operational planning and responsibility assignment, while decision-making practices contributed to strategic alignment. Advanced costing methods, including activity-based and Kaizen costing, were noted for improving cost efficiency. Benchmarking and TDABC emerged as significant predictors of innovation, resource optimization, and enhanced customer satisfaction. Despite its robust methodology, the study’s findings are constrained by reliance on self-reported data and a focus on the banking sector, limiting generalizability. This study highlights the critical role of MAPs in strategic and operational frameworks, advocating for their adoption to achieve sustainable performance and financial outcomes in the banking sector.